A Geospatial Linkage Analysis of Environmental Exposures, Socioeconomic Profile and Health Outcomes Among Women of Reproductive Age in Victoria, Australia - Catherine Helenna Mulyadi; Lisa Hui; Heng Jiang; Mari de Leon; J. C. Nacpil; Yichao Wang; Jason Choi; Suzanne Mavoa; Melvin Barrientos Marzan (Health Promotion Journal of Australia, 2026)
ABSTRACT Issue Addressed Non‐communicable disorders (NCDs) in women of reproductive age (WRA) shape maternal and intergenerational outcomes, yet their area‐level socio‐environmental drivers remain unclear. We examined correlations between socio‐environmental factors and NCDs in WRA. Methods We linked 2021 Australian Census sociodemographic and health variables with postcode‐level environmental exposures, including air pollutants (PM 2.5 , NO 2 , CO, SO 2 , formaldehyde and ozone), land surface temperature and greenness. The NCDs (asthma, diabetes, cancer, mental health and cardio‐renal disease) were expressed per 1000 WRA. Spatial clustering (Moran's I ) and socioeconomic gradients (Wagstaff Concentration Index) were assessed, alongside geospatial regression and clustering analyses. Results NCDs among WRA showed strong socioeconomic patterning. Most disadvantaged postcodes recorded the highest composite NCD burden (323.0 and 227.3 per 1000 in the most disadvantaged and advantaged postcodes respectively), with the steepest inequality for diabetes (Wagstaff = −0.16). Environmental exposures demonstrated spatial clustering but weak associations with health outcomes. Notably, peri‐urban and fringe postcodes experienced higher heat exposure coinciding with socioeconomic disadvantage. Inner Melbourne (with lower heat exposure and more socioeconomic advantage) showed lower NCD burden despite elevated NO 2 and PM 2.5 . Conclusion NCDs among WRA in Victoria are strongly patterned by socioeconomic disadvantage with geographic clustering by environmental exposures. These inequities persist even where most air quality measures remain within regulatory limits, underscoring the disproportionate burden faced by disadvantaged areas. So What Health promotion should prioritise disadvantaged peri‐urban and regional communities through proactive, place‐based policies that address both environmental conditions and the social systems that influence how and for whom those conditions become harmful.